1974
DOI: 10.1002/pssa.2210260216
|View full text |Cite
|
Sign up to set email alerts
|

Transmission, energy distribution, and SE excitation of fast electrons in thin solid films

Abstract: The transmission (TIT) and backscattering (qx) of electrons with energies between 0.5 and 4 keV in thin films of Be, Al, Ge, Cu, and Ag, together with their secondary yields (ST, &), were measured with a three-collector system. The SE efficiencies of backscattered electrons were 3 to 15 times greater than those of incident PE. The energy distributions of the transmitted electrons were measured with a spherical retarding field analyser. Average and most probable energies were obtained. Transmission characteris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
96
0
1

Year Published

1976
1976
2019
2019

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 246 publications
(111 citation statements)
references
References 35 publications
14
96
0
1
Order By: Relevance
“…For higher energy electrons (>10 keV) Fitting gives another relation with an exponent of 1.7. [18] For a test of the influence of this approximation we used both relations to calculate the shelf for an SDD detector at 2.622 keV (Cl-Kα 1 ). The results are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For higher energy electrons (>10 keV) Fitting gives another relation with an exponent of 1.7. [18] For a test of the influence of this approximation we used both relations to calculate the shelf for an SDD detector at 2.622 keV (Cl-Kα 1 ). The results are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For R < D we get again Eqn (14). For R > D, we have to divide the integration range into the ranges 0 < d < D and D < d < R: For the first subrange we get instead of Eqn (14) (18) and for the range…”
Section: Shelf From the Detector Front Layermentioning
confidence: 99%
“…For practical use, e.g., for calculation of energy dependence of coefficient of backscattering η, it is possible to use these values as W min in the model similar to (Liljequist, 1978) and calculate the bacscattering coefficient. Even though this model is theoretically far from reality, the energy dependence of calculated and measured values of backscattering coefficient η (Fitting, 1974) (Figure 2) shows relatively good agreement. By this way it is possible to use for simulation IMFP values from various sources and compare them.…”
Section: Electron Backscatteringmentioning
confidence: 83%
“…However, Whiddington's law was confirmed only for the electron energy range above 10 keV, but not for low energy (≤10 keV) electrons (Young, 1956;Fitting, 1974). Lye and Dekker (1957) have suggested that the energy loss of primary particles is described by the general form,…”
Section: Energy Loss Of Primariesmentioning
confidence: 99%
“…The range-energy relation of electrons in matter for their energy range 0.1 keV < ∼ E 0 < ∼ 1 MeV can be approximated by (cf. Fitting, 1974) R (E 0 ) = 50 nm ρ 10 3 kg m −3…”
Section: Energy Loss Of Primariesmentioning
confidence: 99%